2016
DOI: 10.21831/jptk.v23i2.12296
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Motivation, Learning Styles, Teacher Leadership, and Teaching Intensity on Students’ Leaning Outcomes

Abstract: This study aims to determine the correlation and the contribution of motivation, learning styles, teacher leadership, and the intensity of teaching on the learning outcomes of X grade students in Mathematics at Vocational High Schools. This study is an ex-post facto with a total sample of 234 students. The data is collected by questionnaire and analyzed by descriptive statistics as well as correlation and multiple regression with significance level of 5%. The analysis shows that the students’ motivation and le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 0 publications
0
5
0
3
Order By: Relevance
“…This motivation helps students improve learning outcomes (Retnawati et al, 2019). Learning motivation can influence and have a relationship with student learning outcomes (Sulistiyarini & Sukardi, 2016). Students active in learning give students many opportunities to make improvements and identify abilities.…”
Section: Math Learning Outcomes With Aflmentioning
confidence: 99%
“…This motivation helps students improve learning outcomes (Retnawati et al, 2019). Learning motivation can influence and have a relationship with student learning outcomes (Sulistiyarini & Sukardi, 2016). Students active in learning give students many opportunities to make improvements and identify abilities.…”
Section: Math Learning Outcomes With Aflmentioning
confidence: 99%
“…The results of the study on the teaching style of the teacher through this AR teaching kit found that the teaching style of the teacher was positive motivation in student learning [35]. According to Ngah [36], teaching and learning processes in the classroom need to be gradually designed according to the level of the students thus students can easily follow the contents of the lesson.…”
Section: Resultsmentioning
confidence: 99%
“…Selain itu, beberapa temuan penelitian membuktikan bahwa motivasi yang dimiliki oleh anak didik memiliki pengaruh yang positif terhadap hasil pembelajaran, sebagaimana temuan Sulisttiyarni dan Sukardi yang membuktikan bahwa hasil pembelajaran matematika salah satunya dipengaruhi oleh motivasi peserta didik (Sulistiyarini & Sukardi, 2016). Temuan lainnya ialah hasil penelitian Asvio dan kawan-kawan yang menegaskan bahwa selain lingkungan belajar motivasi memberikan dampak yang baik terhadap pembelajaran pendidikan agama Islam (Asvio et al, 2017), Penelitian Taurina juga dapat dilihat sebagai acuan dalam menarik kesimpulan bahwa motivasi siswa sangat besar pengaruhnya terhadap hasil belajar (Taurina, 2015).…”
Section: Pendahuluanunclassified